Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T17:30:54+01:00
A.
2x-(1-4x)=2+(8x-5)
2x-1+4x=2+8x-5
2x+4x-8x=2-5+1
-2x=-2
x=1

b.
4-2(5-x)=x-4(x-1)
4-10+2x=x-4x+4
2x-x+4x=4-4+10
5x=10
x=2

c.
7-(3x+4)=(x+1)-(2x+4)
7-3x-4=x+1-2x-4
-3x-x+2x=1-4-7+4
-2x=-6
x=3

d.
x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3
x+x-3x+2x=3-3+4
x=4
2010-02-01T17:40:52+01:00
A.2x-(1-4x)=2+(8x-5)
2x-1+4x=2+8x-5 |+1
6x=8x-2 |-8x
-2x=-2 |/-2
x=1

b.4-2(5-x)=x-4(x-1)
4-10+2x=x-4x+4 |+6
2x=-3x+10 |+3x
5x=10 |/5
x=2

c.7-(3x+4)=(x+1)-(2x+4)
7-3x-4=x+1-2x-4 |-3
-3x=-x-6 |+x
-2x=-6 |/-2
x=3

d.x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3 |+1
2x=x+4 |-x
x=4